Water and sediment quality of Ashtamudi estuary, a Ramsar site, southwest coast of India—a statistical appraisal - K. Narendra Babu; P. K. Omana AND Mahesh Mohan
Ashtamudi estuary, situated on the southwest coast of India, is enormously affected by anthropogenic interventions. Physicochemical quality of water and sedimentological features of the estuary are evaluated during monsoon and nonmonsoon seasons to elucidate its quality vari- ations and to link the same with existing en- vironmental scenario. The whole data has been factorized using principal component analysis for extracting the total variability and linear relation- ships existing among a set of different physic- ochemical parameters of the backwater system. In PCA, high loadings were obtained for con- ductivity, salinity, fluoride, calcium, magnesium, sulfate, boron, and pH. The results were revealed that all the physicochemical processes depend upon seasonal fluctuation of freshwater input and seawater intrusion. Wide spatial concentration fluctuations of organic carbon and iron in bot- tom sediment have been noticed and both con- stituents reveal good correlation with sediment texture. The results showed high deterioration of the physicochemical quality of water during non- monsoon season with respect to monsoon season